Entre paisagens sulinas: fotografias para criação de novos mundos possíveis - Azevedo, Cláudio Tarouco de (Paralelo 31, 2021)
Ensaio visual do artista brasileiro Cláudio Azevedo  que contrasta fotografias da paisagem sulina no Brasil.   Palavras-chave: Paisagem sulina. Fotografia. Educação ambiental. Arte e meio ambiente.  Between Southern Landscapes: Photographs for creating new possible worldsAbstract: Visual essay by the Brazilian artist Cláudio Azevedo which contrasts photographs depicting the landscape in southern Brazil.  Keywords: Southern landscape. Photography. Environamental education. Art and Environment.